Shio Kusaka & Jonas Wood - Benschop, Jurriaan 1963-; Swarts, Suzanne 1979- (Voorlinden, 2017)
Although Kusaka and Wood work independently, their mutual influences are palpable. This is hardly surprising: they not only live together but also share a single studio. Their art is as intertwined as their lives. Kusaka's work consists of elegant pots and vases in all shapes and sizes. It reflects diverse influences: traditional Japanese techniques, for instance, but also the geometrical patterns of contemporary artists such as Agnes Martin. Wood's paintings of plants and interiors blur the lines between figurative and abstract art. The recognizable, distorted perspectives in his plant still lifes and portraits testify to influences from areas of art history as distinct as cubism, pop art, and artists such as David Hockney.0The mutual influences are immediately apparent in Wood?s paintings of Kusaka?s pots and objects, which in turn borrow patterns from his work such as elements of sport and everyday shapes. What we see is a constant visual dance and an ever-evolving interaction between subject and object, between observer and observed. When we look a little further, we also see a mutual fascination with geometry on the one hand and imperfection on the other. While Wood's perspectives are always slightly askew and his shapes two-dimensional, her pots and vases are seldom symmetrical or entirely round. Exhibition: Museum Voorlinden, Wassenaar, The Netherlands (30.09.2017-07.01.2018)
Ter gelegenheid van de tentoonstelling "Shio Kusaka & Jonas Wood" in museum Voorlinden, Wassenaar, Oktober 2017. - Genaue Ausstellungsdaten ermittelt: van 30 september 2017 tot en met 7 januari 2018
Keywords: Wood, Jonas -- 1977-; Kusaka, Shio -- 1972-; Ausstellungskatalog -- Museum Voorlinden -- 30.09.2017-07.01.2018 -- Wassenaar; Bildband